PERLINDUNGAN KONSUMEN TERHADAP PEMBELIAN KOSMETIK ILEGAL MELALUI SITUS ONLINE - Han, David; Ukas (SCIENTIA JOURNAL, 2021)
In the current era of digitalization, cosmetics have become a very important part of the needs of society, especially for women who are the main target of the current cosmetic industry market. Not only women in today's era but men also participate in using various cosmetic products. Where these products are believed to increase a person's confidence due to the polish produced from these cosmetic products. This research is a normative legal research, namely library law research that refers to consumer protection legislation. The focus of this research is to examine and analyze the problem of a violation of the law for rogue business actors for the circulation of an illegal product that is sold freely through online sites based on the provisions of the consumer protection law. Based on the results of this study, it can be seen that the legal protection for cosmetic users who are not registered with BPOM where the Government has issued legislation related to consumer protection. However, until now consumers or users of cosmetics have not been fully protected because the government has not been able to stop the circulation of these cosmetics. These cosmetic products are spread due to several factors such as the lack of consumer education and knowledge related to dangerous/illegal cosmetics, online shopping as an alternative for consumers during a pandemic, and the difficulty of choosing cosmetics from the dangers of illegal cosmetics, especially through online buying and selling sites.